(4-3)m=-1

Simple and best practice solution for (4-3)m=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4-3)m=-1 equation:


Simplifying
(4 + -3) * m = -1

Combine like terms: 4 + -3 = 1
(1) * m = -1

Solving
1m = -1

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Divide each side by '1'.
m = -1

Simplifying
m = -1

See similar equations:

| (-p^5q^4)+(4p^5q^4)= | | 5,305/x=11,65 | | 7x-8(x+3)=2 | | 13/6x=1/10-10/9 | | 3x=-4x-14 | | 11=v/25+12 | | Y=-143.3(64)+1823.3(8)+6820 | | 50-3x=9-8x | | -32+5x=26 | | (6v-9)/3 | | F(x)=2x^2-4x-1 | | 3x-(x+6)=16 | | 7(w-5)=-5w+1 | | 3k+4=28 | | 2/3x=-4/27 | | K=mc^2 | | 66=-15x+6 | | 114/12 | | X/12+5/6=5/24 | | 2x+(45x-14)=1-x | | -3x+40=x^2 | | -m/4=-3/4 | | 6(w-3)-8w=-16 | | -143.3(10)(10)+1823.3(10)+6820= | | 49*7/6 | | 6+4m-5=17 | | 7/x+2+1/x-1=4 | | 9x=-23 | | 204/90 | | -2340x^2+34368x-118675=0 | | A=h*g | | 2m+14-14=7kx-14 |

Equations solver categories